2016
DOI: 10.17269/cjph.107.5437
|View full text |Cite
|
Sign up to set email alerts
|

Towards a shared understanding: Perspectives from Toronto’s first media forum for suicide prevention

Abstract: Media reporting on suicide may have harmful and/or protective effects on deaths by suicide, depending on the nature of the coverage. Canada's first forum on this important issue was held in Toronto on November 6, 2015. Participating in the forum were public health policy-makers, mental health and suicide prevention experts and senior media representatives. This commentary summarizes the content of the forum and highlights the need for ongoing collaboration between suicide prevention experts and media professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
(8 reference statements)
0
20
0
4
Order By: Relevance
“…While guidelines typically improved the quality of reporting, journalists' awareness, use and opinion of guidelines was generally low, and approaches centred on media consultation and collaboration had the greatest success (Bohanna and Wang, 2012). Media professionals may legitimately argue that it is in the public interest to report on newsworthy suicides and some could be sceptical about the association between media reports and imitative suicidal behaviour, viewing any restrictions as censorship that perpetuates 'taboos' around suicide (Bohanna and Wang, 2012;Collings and Kemp, 2010;Sinyor et al, 2016). To inform the development of national guidelines, further research should examine the perspectives of media professionals in India in relation to suicide reporting to enable a critical engagement with their concerns, as has been done elsewhere (Cheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While guidelines typically improved the quality of reporting, journalists' awareness, use and opinion of guidelines was generally low, and approaches centred on media consultation and collaboration had the greatest success (Bohanna and Wang, 2012). Media professionals may legitimately argue that it is in the public interest to report on newsworthy suicides and some could be sceptical about the association between media reports and imitative suicidal behaviour, viewing any restrictions as censorship that perpetuates 'taboos' around suicide (Bohanna and Wang, 2012;Collings and Kemp, 2010;Sinyor et al, 2016). To inform the development of national guidelines, further research should examine the perspectives of media professionals in India in relation to suicide reporting to enable a critical engagement with their concerns, as has been done elsewhere (Cheng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examining adherence to Mindset's 14 specific recommendations in the aftermath of a celebrity suicide found that most recommendations were followed (range of adherence was 65% to 99% of articles), except for the recommendation to tell people considering suicide how they can get help (present in only 27% of articles). 48 The original CPA position paper on media reporting and suicide 1 garnered controversy from some who expressed scepticism about the evidence base for suicide contagion, 49 and argued that perceived efforts to suppress suicide-related stories are counter-productive. 50 In the interim, there has been increased engagement between mental health professionals and the media via informal dialogue surrounding specific reports, through symposia at the CPA annual meeting, and during and after Canada's first media forum for suicide prevention, held in Toronto in November, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…49 In part due to a greater public desire for information about mental health, journalists are increasingly interested in covering issues related to mental health, including suicide, in a respectful and destigmatizing manner. 49 Most suicide deaths are not newsworthy and the media are sensitive to concerns about contagion; however, deciding when and how to cover suicide is a delicate balancing act. 49 Rather than telling journalists how to do their jobs, consensus is that the mental health community needs to work collaboratively with the media and provide them with the best available information to make those difficult decisions, and to provide context and help mitigate risks of contagion when the decision is to proceed with a report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 A detailed understanding of the specific aspects of media reports that may provoke suicide contagion is needed to help the media make these decisions; however, evidence identifying the "active ingredients" in media reporting that may mediate suicide contagion or adaptive behaviour remains limited. The studies above have established an evidentiary starting point from which the relative harmful or protective contributions of specific elements in media reports may begin to be unpacked.…”
mentioning
confidence: 99%